WOMEN’S EDUCATION IN INDIA – THE POWER OF A SECOND CHANCE - Pillai, Daphne; Joy, Dr. (PEOPLE: International Journal of Social Sciences, 2017)
Education plays a major role in the sustainable development of a nation. The global literacy rate for all people aged 15 and above is 86.3% with the global literacy rate for all males at 90.0% and the rate for all females at 82.7%. The rate varies throughout the world with developed nations having a rate of 99.2% (2013). In many developing countries, despite gains in educational attainment, learning levels are abysmally low, both when compared with developed countries and with national learning standards (Pritchett, 2013). Over 75% of the world’s 781 million illiterate adults are found in South Asia, West Asia and sub-Saharan Africa and women represent almost two-thirds of all illiterate adults globally. (Source: UNESCO Institute of Statistics, 2015). Although India has raised its literacy rate in 2011 to 74.04% from 12% at the time of Independence in 1947, it still lags behind the world average literacy rate of 86%. Besides this there is a wide gender disparity in the literacy rate in India: effective literacy rates (age 7 and above) in 2011 were 82.14% for men and 65.46% for women (source: Census 2011). One of the main reasons for this is the alarming rate of school dropouts among girls due to culture, custom and poverty. Though women today have achieved many milestones, women’s education has yet to reach its full potential. “The Power of a Second Chance" is an opportunity given to those women who missed out on the first chance in education during their childhood. This research paper, through a study conducted of 145 women school dropouts, attempts to highlight some of the reasons for girls dropping out of school and the impact of lack of education on their social and financial status. It discusses the socio-economic barriers to their progress. It also makes recommendations on how these women can be empowered with a second chance through literacy programs and income-generating skills.